Bacterial Pathogenesis and Antibacterial Control 2018
DOI: 10.5772/intechopen.72526
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Metallic Nanoparticles

Abstract: Metallic nanoparticles (NPs) for medical applications have been documented since earlier times. Advancement in modern medicines results in an increase in utilization of NPs for medical purposes due to their antibacterial, antiviral, antifungal, anti-inflammatory, and antiangiogenic properties. In this chapter, three metallic NPs are studied extensively as powerful nanoweapons for the destruction of bacteria. Recent research gives evidence that metallic NPs are very effective in supporting antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…They have a substantially larger surface-area-to-volume ratio resulting in increased toxicity compared to the metal, alongside improved optical properties making them a desirable replacement. [2][3][4][5] Pathogenic microbes may be transmitted directly from person-to-person or indirectly via contamination of surfaces leading to both healthcare-acquired infections (HAIs) and community-acquired infections (CAIs). [6][7][8] The exact mechanism of microbial death from copper is controversial and the significance and relative contribution of each proposed mechanism are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They have a substantially larger surface-area-to-volume ratio resulting in increased toxicity compared to the metal, alongside improved optical properties making them a desirable replacement. [2][3][4][5] Pathogenic microbes may be transmitted directly from person-to-person or indirectly via contamination of surfaces leading to both healthcare-acquired infections (HAIs) and community-acquired infections (CAIs). [6][7][8] The exact mechanism of microbial death from copper is controversial and the significance and relative contribution of each proposed mechanism are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CuO-NPs were reported to have potent antimicrobial activity against Escherichia coli and Staphylococcus depending on the concentration and particle size. 8 Harikumar & Aravind 9 found that copper nanocomposites can inhibit E. coli and that its effect increased with the increase of concentration and contact time. The antimicrobial property of lm containing heat treated CuO-NPs against the growth of E. coli were higher than the lm containing NaBH 4 -treated CuO-NPs.…”
Section: Introductionmentioning
confidence: 99%
“…and ability to be effective at much lower dosage 9,10 . For instance, preliminary evaluations showed that silver nanocluster/ silica composite coating on facial masks had viricidal effects against SARS-CoV-2 11 .…”
Section: Focus | Comment Comment | Focusmentioning
confidence: 99%